Jealousy coping strategies in romantic and marriage relations - Fourmanov, Igor (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
In article are studied interactive and behavioral reactions to jealousy situation of depending on a role in partner relations in early adulthood. The study suggest that the reactions of integrative communications and compensation/substitution are more often used without dependence from a role in jealousy situation. In romantic relations reaction to a jealousy situation is defined by value of the partner, and in marriage – value of relations.
Keywords: jealousy; communicative reactions to jealousy; partner and marriage relations